Ephemeral Architectures for Celebrating Happiness: Symbolic and Persuasive Values of an Archetypal Example - Fernández-Paradas, Antonio-Rafael; Rodríguez-Martín, Nuria (ANDULI, Revista Andaluza de Ciencias Sociales, 2023)
After more than half a century of war, the announcement of the end of the Third Carlist War resulted in a veritable explosion of happiness and collective euphoria in Spain at the end of the 19th century. On 20 March 1876, Alfonso XII, nicknamed "The Peacemaker", made his triumphal entry into Madrid. The press of the time described the event as one of the happiest in the history of Spain. The aim of this paper is two fold: to contextualize and analyze the importance of the festivities and ephemeral decorations as a reflection of the social happiness of the moment and to analyze the symbolic and persuasive values of one of the ephemeral architectures erected for the occasion. As a final result, we demonstrate how ephemeral architecture and festivals were a source of happiness in the battered Spanish society of the last third of the 19th century, generating social welfare and happiness through art and the nationalist exaltation of the monarchy.